2006
DOI: 10.1175/jpo2805.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Delaware Bay Buoyant Outflow: Comparison with Observations

Abstract: Coastal buoyant outflows from rivers and estuaries previously have been studied with field research, laboratory experiments, and numerical models. There is a dire need to evaluate model performance in light of coastal current observations. This research simulates the Delaware Bay outflow and compares results with observations of estuarine and shelf conditions. Observations include an estuarine salinity climatology, a record of freshwater delivery to the shelf, coastal current salinity mappings, and surface dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 48 publications
2
54
1
Order By: Relevance
“…The Estuary is 210 km long and comprises tidal reaches of the Delaware River (starting in Trenton, New Jersey) and all of the Delaware Bay [18]. The width of the estuary increases toward the mouth to 18 km, which extends between Cape May and Cape Henlopen.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The Estuary is 210 km long and comprises tidal reaches of the Delaware River (starting in Trenton, New Jersey) and all of the Delaware Bay [18]. The width of the estuary increases toward the mouth to 18 km, which extends between Cape May and Cape Henlopen.…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, the application of an average river discharge can be an appropriate representation of the average forcing throughout the power plant life cycle. There are other tributaries flowing into the estuary between the mouth and upstream boundary, but not included, as their effects are considered localized [18] and not significant to the goals of this study.…”
Section: River Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects the small-scale discharge of the Connecticut River by moving the plume to the east of the river mouth on an ebb tide and to the west on a flood tide (Whitney and Garvine, 2006). Using a numerical model, Guo and Valle-Levinson (2007) analyzed tidal effects on an outflow plume in Chesapeake Bay and concluded that a bottomadvected plume occurred due to tidal forcing whereas a surface-advected plume developed without tidal forcing.…”
Section: Introductionmentioning
confidence: 99%
“…For the high-volume river outflow of the Columbia River, plume mixing was strongest near the tidal plume front, which exchanges nutrients and sediments (Orton and Jay, 2005). Although some tidal forcing effects on freshwater plumes have been considered (Wiseman and Garvine, 1995;Orton and Jay, 2005;Whitney and Garvine, 2006;Guo and Valle-Levinson, 2007), the majority of studies have focused on the effects of wind forcing on plumes with large K values.…”
Section: Introductionmentioning
confidence: 99%